Recollections of sexual socialisation among marginalised heterosexual black men - Dunlap, Eloise (2013)
This paper describes the sexual socialisation process of marginalised, drug-using heterosexual black men, focusing primarily on the sources and content of sexual information. Analysing qualitative interview data, we discovered that the men in our sample both learn about sex and become sexually active at an early age. They most often learn about sex from the media and least often learn about sex from family members. The content of sexual information varies in specifics, but overall tends to equate sex with pleasure, encourage sexual activity with multiple partners, and emphasise using protection. Our goal is to use this data to better understand how sexual socialisation contributes to the prevalence of multiple sexual partners and high rates of HIV among heterosexual black men in order to inform future risk-reduction intervention programmes.